Increased plasma levels of lipocalin 2 in mild cognitive impairment - Choi, Jihye; Lee, Ho-Won; Suk, Kyoungho (Journal of the neurological sciences, 2011)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by an irreversible cognitive decline and neuronal loss associated with neurofibrillary tangles and senile plaques. Mild cognitive impairment (MCI) is a prodromal stage of AD and is associated with memory loss and a high risk of developing AD. Lipocalin 2 (LCN2) is an acute phase protein. Our previous studies have shown that exposure to inflammatory stimuli resulted in elevated LCN2 levels in brain microglia and astrocytes implicating LCN2 in brain inflammation. Therefore, we hypothesize that there may be a significant change in the plasma LCN2 levels in patients with MCI and AD when compared to healthy control subjects. Forty-one patients with MCI, 62 patients with AD and 38 healthy elderly control subjects were recruited for this study. They were given a comprehensive battery of neuropsychological tests including a mini-mental status examination (MMSE) and clinical dementia rating (CDR). A variety of clinical information was collected from the semi-structured questionnaire administered. The LCN2 levels were measured using a specific enzyme-linked immunosorbent assay in the plasma, which had been collected early in the morning after overnight fasting. The LCN2 levels were significantly higher in MCI patients compared to the healthy control subjects and AD patients [control vs. MCI (p = 0.005); MCI vs. AD (p = 0.009)]. There was a significant negative correlation between the LCN2 levels and CDR scores (r = − 0.245, p = 0.014), and there was a positive correlation between the LCN2 levels and MMSE scores (r = 0.317, p = 0.001) among all of the MCI and AD patients. MCI represents a prodromal stage of AD, and inflammation occurs as one of the earliest pathological events in AD. Thus, increased plasma LCN2 levels during MCI could be helpful in predicting the progression from MCI to AD.